LEARNING COMPETENCY ACQUISITION, AND WORKSHEET USEFULNESS AND DIFFICULTY AS PREDICTORS OF STUDENTS’ PERFORMANCE IN THE NEW NORMAL - Agua, Breix Michael; Patinga, Myline (International Journal of Education, 2024)
The Philippine K-12 Enhanced Basic Education Program aimed to produce holistically developed students imbued with 21st-century skills. In response to these needs, the Commission on Higher Education issued the New General Education Curriculum, which includes Mathematics in the Modern World (MMW) as a tool for understanding modern living. Teachers face challenges teaching MMW as a new course, and instructional materials are crucial for effective teaching.  The Caraga State University faculty of the Mathematics Department developed instructional material for MMW, and this study examined the impact of it on students' performance. The study investigated the acquisition of learning competencies, difficulties, and usefulness of the developed worksheets in Mathematics in the Modern World (MMW) as predictors of students' performance. The research used a causal design. Using proportionate random sampling across sections of students who took the MMW course for the second semester of the Academic Year 2021-2022 at the Caraga State University main campus, 258 students were selected as the research participants. The results showed that the students have a high acquisition of learning competencies in the knowledge, skills, and values category. Students found the worksheets moderately challenging and rated them as useful. Students who received excellent and very good grades highly acquired the intended learning competencies, followed by those who received passing grades, and those who received below passing grades had the lowest learning competency acquisition mean. Using Pearson r correlation, learning competency acquisition, difficulty level, and usefulness level of the developed worksheets were significantly correlated with students' Mathematics in the Modern World performance with p-values 0.001,0.001, and 0.009, respectively. However, using regression analysis, only the worksheets' difficulty and usefulness were predictors of students' performance, suggesting a thorough review of these aspects as they influenced students' performance.